Cycles of conditional cooperation in a real-time voluntary contribution mechanism - Maria Vittoria Levati; Ro'i Zultan (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper provides a new way to identify conditional cooperation in a real-time version of the standard voluntary contribution mechanism. Our approach avoids most drawbacks of the traditional procedures because it relies on endogenous cycle lengths, which are defined by the number of contributors a player waits before committing to a further contribution. Based on hypothetical distributions of randomly generated contribution sequences, we provide strong evidence for conditionally cooperative behavior. Moreover, notwithstanding a decline in contributions, conditional cooperation is found to be stable over time.
Keywords: C72; C92; H41; 330; Public goods game; Real-time protocol; Information feedback; Conditional cooperation; Simulations; Öffentliches Gut; Finanzierung; Nichtkooperatives Spiel; Kooperation; Trittbrettfahrerverhalten; Test; Simulation